Política de avaliação e seleção de doações em acervos particulares a serem incorporados às Bibliotecas da Universidade Federal de Santa Maria, RS - Leipnitz, Fernando (2017)
This work, by causing the dialogue between the private library and the university library, to propose an acquisition and management of private collections policy and a model contract for the donation of private collections to the libraries of the Federal University of Santa Maria. To do so, is used the analytical-comparative methodology to explain the concept of special collections, exemplifying some universities that guard private collections in their various characterizations, and types of management applied to these collections. It discusses the importance of the development of collections in university libraries, with emphasis on the evaluation and selection of books received in donations. Debate the institutionalization of private bibliographic collections in universities seeking to list the various issues that need to be studied in order to be able to effect such a process. As a result of the analysis, it proposes a policy of evaluation and selection of bibliographical works received in donation, listing criteria that guide the reception and technical treatment of the material. Also, it guides the importance of the analysis of the biography of the donor when a whole particular collection is received. Due to the relevance of this study and the complexity of the incorporation of private libraries in university libraries, it was necessary to prepare a proposal of donation contract so that the Federal University of Santa Maria can receive private collections that deals with property and rights issues and make it public for research.